Branje Jamnice v času socialnih sprememb - Perenič, Urška (Jezik in slovstvo, 2010)
Prežih's "neighbourhood novel" Jamnica (1945), which was written under the influence of foreign and Slovene literary classics as well as of the genre model of the rural novel, met with success on its publication. In this collective novel the village community retains above all the various folklore forms of sociability, but rather than simply being narrative ornamentation the descriptions of these forms are woven into the social message of the novel. Another characteristic in the attachment of the members of the community to the land, a kind of natural vitalism. In a time of economic crisis and on the brink of the Second World War, the survival strategy of the comunity leads to a "social experiment", i.e., entering into a social pact between the landowners and the crofters.
Keywords: Prežihov Voranc, 1893-1950; Slovene literatue; Slovene literature; slovenska književnost; novels; socialni realizem; 20. st.; romani; roman soseske; Prežihov Voranc: Jamnica; kolektivni subjekt